The influence of organization atmosphere and school leadership on teacher performance in senior high school - Tri Handayani; Happy Fitria; Yenny Puspita (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This objective of the study was to know 1) the influence of organization atmosphere on the teacher performance, 2) the influence of school leadership on the teacher performance and 3) the influence of organization atmosphere and school leadership on the teacher performance. This research uses quantitative methods. The population was the all teachers at Senior High School with the total 69 teachers and 1 headmaster. The Sampling was use random sampling technique at 25 respondents and multiple linear regression formula. Data collection is done by questionaire and documentations. Data were analyzed descriptively using SPPS Version 20 for windows. From the results of the study it can be concluded that 1) there was an influence of organization atmosphere on the teacher performance, 2) there was an influence of school leadership on the teacher performance and 3) there was an influence of organization atmosphere and school leadership on the teacher performance.